Demand Curves and the Pricing of Money Management - Christoffersen, Susan E. K.; Musto, David K. (Review of Financial Studies, 2002)
One reason why funds charge different prices to their investors is that they face different demand curves. One source of differentiation is asset retention: Performance-sensitive investors migrate from worse to better prospects, taking their performance sensitivity with them. In the cross-section we show that past attrition significantly influences the current pricing of retail but not institutional funds. In time-series we show that the repricing of retail funds after merging in new shareholders is predicted by the estimated effect on its demand curve. This result is robust to other influences on repricing, including asset and account-size changes.